Managers in the transformation process of Eastern Europe: A case of Slovenia - Danijel Pučko; Matej Lahovnik (Journal for East European Management Studies, 1997)
The article offers results of the empirical research project on strategic restructuring processes in Slovenian enterprises. The changes in the positions of managing directors of enterprises and developments of the value systems and objectives of Slovenian managers are discussed. The authors show a comparison of the relevant values and objectives of Slovene managers and their Western European counterparts. They briefly describe the differencies between both groups of managers. The research has tried to identify the managing directors' perception of the competitive advantage's factors and the business strategies that are being implemented in the Slovenian enterprises. Finally, the managing directors' assessments of the length of the strategic restructuring process in the Slovenian old firms are presented. – – Der Artikel handelt von den Änderungen in den Führungspositionen der ehemaligen slowenischen Firmen, der Entwicklung des Bewertungssystems und den Zielen der slowenischen Geschäftsführer. Es folgt eine Gegenüberstellung der relevanten Bewertungen und Ziele zwischen den slowenischen und westeuropäischen Geschäftsführern, wobei die Unterschiede zwischen den beiden Geschäftsführergruppen aufgezeigt werden. Weiter wird ein Vergleich gezogen zwischen den Konkurrenzfaktoren, die als das wichtigste Element des strategischen Handelns bezeichnet werden können. Außerdem werden die Geschäftsstrategien beschrieben, die in den slowenischen Firmen umgesetzt worden sind. Abschließend wird eine Prognose über die Dauer der strategischen Umstrukturierungsprozesse abgegeben.
Keywords: 650